Pengembangan Modul Berbasis Pendekatan Konstektual pada Materi Menulis Iklan di Kelas VIII SMP 2 Padangsidimpuan Sumatera Utara - Toras Barita Bayo Angin; Syahrul R; Agustina . (Fakultas Bahasa dan Seni UNP, 2015)
Abstract: The background of this research was the problem at the eighth grade students of SMP Negeri 2 Padangsidimpuan about advertisement writing skill. The problems were less precise to make title creation, to made advertisement text, to made picture visualization, and giving slogan. To solve this problem, it needed learning module which was developed based contextual approach. The type of this research was development by applying 4D (define, design, develop, and disseminate) Instrument of this research used the module validity questionnaire, the module practicality questionnaire for teacher and students, and test sheet for task. Module had been tested to the eighth grade students of SMP Negeri 2 Padangsidimpuan which had been previously validated. The data analyzing technique used descriptive statistics to get percentage practicality and effectiveness of learning module.The result of this research was a module development based contextual in advertisement writing subject where: (1) designed module was valid, it was categorized “very valid” which include valid in terms of content, language, presentation and graphics (2) designed module was practically to be used which include practically in terms of easy and time (3) designed module was effective in increasing students’ activity and students’ motivation in advertisement writing subject, it could be seen from students’ activity and students’ achievement by using test performance. Keywords: module, writing advertisement, Four-D model